2018
DOI: 10.1016/j.ajic.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Social media and outbreaks of emerging infectious diseases: A systematic review of literature

Abstract: Although academic studies of EID communication on social media are on the rise, they still suffer from a lack of theorization and a need for more methodologic rigor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
203
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(214 citation statements)
references
References 41 publications
4
203
1
6
Order By: Relevance
“…Features specific to COVID-19 which are responsible for the mental health problems include the speculations about its mode of transmission, rapidity of spread and lack of definitive treatment protocols or vaccine. Compared to the outbreak of SARS, widespread global connectivity and extensive media coverage are leading to the catastrophic reactions secondary to the outbreak (Tang et al, 2018;Ho et al, 2020) Research in the past had shown that epidemics can cause severe and variable psychological effects on people. In the general population, this can lead to the development of new psychiatric symptoms, worsening of pre-existing illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Features specific to COVID-19 which are responsible for the mental health problems include the speculations about its mode of transmission, rapidity of spread and lack of definitive treatment protocols or vaccine. Compared to the outbreak of SARS, widespread global connectivity and extensive media coverage are leading to the catastrophic reactions secondary to the outbreak (Tang et al, 2018;Ho et al, 2020) Research in the past had shown that epidemics can cause severe and variable psychological effects on people. In the general population, this can lead to the development of new psychiatric symptoms, worsening of pre-existing illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies of Twitter during COVID-19 were revealed by our MEDLINE search, several previous studies have suggested a role for Twitter data during other public health outbreaks including Middle East respiratory syndrome, 23 SARS, 24 Ebola virus disease, 15 Zika virus, 25 H1N1 ('swine flu') 26 and H7N9 ('avian flu'). 27 Suggested roles for Twitter include infectious disease surveillance, predicting spread of disease, dissemination of public health information and assessing public views toward public health outbreaks. 15,[23][24][25][26][27]…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…27 Suggested roles for Twitter include infectious disease surveillance, predicting spread of disease, dissemination of public health information and assessing public views toward public health outbreaks. 15,[23][24][25][26][27]…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Extensive media coverage of the epidemic can now influence the public's physical and psychological response to the infectious disease threat, which may inevitably amplify apprehension while serving as a pivotal tool to encourage precautionary and preventive measures [9].…”
Section: Introductionmentioning
confidence: 99%